Textual cohesion and procedural pragmatics in Arabic digital banking discourse: A pragmatic-linguistic way to samples from UAE banking applications - Meqdad, Saad Abd Allah; Issa, Hamzeh Abu; AbuGharbiah, Essam Eid; Al Zaabi, Talal Ahmed Salim; Al Riyami, Ali Hamed Ali (Research Journal in Advanced Humanities, 2026)
This study puts forward a pragmatic-linguistic angle toward textual cohesion in the Arabic part of banking applications. Here, it is treated as procedural digital discourse, not only that it sends information, but it sort of leads the user toward certain financial actions , and in the same time it shapes how people understand, trust, and feel secured. The work starts from the assumption that short banking messages e.g. verification, alert, confirmation, error, and transfer notices, are not kind of standalone verbal pieces. Instead, they work as links in an interactive path where textual organization meets user experience requirements and also digital-security constraints. For the study, a descriptive-analytical method is adopted. It relies on Arabic banking phrases and texts that are available via the official digital channels of selected UAE banks as well as Islamic financial institutions, and these are used as discourse material fit for pragmatic, and text-linguistic examination. The analysis looks at referential cohesion, lexical cohesion, conjunction, procedural sequencing, pragmatic consistency, and linguistic security. The results suggest that the “power” of digital banking text is not assessed by grammatical accuracy only. It is rather about how well it lowers confusion, holds terminology stable, arranges the steps, signals risk, and finally directs the user to the correct action. Overall, the study concludes that Arabic banking-application content forms a promising field for text linguistics and digital pragmatics, and that improving it needs teamwork among linguists, content editors, user-experience designers , and digital-security specialists.